2011
DOI: 10.1007/s00415-011-6369-2
|View full text |Cite
|
Sign up to set email alerts
|

Clinical applications of susceptibility weighted imaging in patients with major stroke

Abstract: Susceptibility weighted imaging (SWI) is a newly developed magnetic resonance (MR) protocol. Recent studies have found that SWI may be useful in the field of cerebrovascular diseases, especially for detecting the presence of prominent veins, microbleeds and the susceptibility vessel sign (SVS). Some authors have even suggested that SWI can be used to predict outcome. We conducted a prospective study of patients hospitalized with middle cerebral artery territory infarction receiving MRI within 2 days of stroke … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
89
1
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(102 citation statements)
references
References 19 publications
(32 reference statements)
4
89
1
2
Order By: Relevance
“…It has been reported in the literature [24] that a magnetic resonance angiogram (MRA) and SWI can be used to detect an intracranial artery embolus in a patient with an acute ischemic stroke. Compared with an MRA, however, a susceptibility vessel sign (SVS) is more likely to indicate a clogged artery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported in the literature [24] that a magnetic resonance angiogram (MRA) and SWI can be used to detect an intracranial artery embolus in a patient with an acute ischemic stroke. Compared with an MRA, however, a susceptibility vessel sign (SVS) is more likely to indicate a clogged artery.…”
Section: Discussionmentioning
confidence: 99%
“…While Chen and Ni [8] suggested that PDM could replace PET-CT. Additionally, gadolinium, which is introduced during perfusion scans, can induce an allergic reaction in some patients. Huang et al [9] believe that gadolinium may cause nephrogenic systemic fibrosis (NSF), which may trigger renal dysfunction. Kuo et al [10] have also suggested that any contrast agent may cause NSF.…”
Section: Introductionmentioning
confidence: 99%
“…4,8 However, it was difficult to differentiate cortical veins from leptomeningeal collaterals because there were no obvious morphologic differences between them. 9 Additionally, the anatomic variability of cortical veins also contributes to reduced interrater agreement when assessing the cortical veins. In contrast to cortical veins, leptomeningeal collaterals do not interfere with the assessment of deep cerebral veins, and anatomic variation in deep veins is less prevalent.…”
mentioning
confidence: 99%
“…7,59 SWI can effectively determine the CVS to detect arterial occlusion 49 and the change in CVS preand postadministration of the thrombolytic agent to assess reperfusion levels. 7 Although CVS measurements offer precise information on the thrombotic region, a simpler detection method involves the presence of dilated and hypointense cortical vessels on SW images.…”
Section: Thrombosis Detectionmentioning
confidence: 99%
“…A limited collection of studies has examined the ability of SWI to monitor outcome in stroke patients; 6,7,49,56,64 however, the method of monitoring stroke outcome has varied greatly between studies. Bai et al 6 have suggested that a greater amount of CMBs on SWI after reperfusion is predictive of a better outcome.…”
Section: Monitoring Outcome In Strokementioning
confidence: 99%